2020
DOI: 10.1039/d0ce01004a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal engineering of coordination-polymer-based iodine adsorbents using a π-electron-rich polycarboxylate aryl ether ligand

Abstract: The efficient capture and storage of radioactive iodine isotopes are important in nuclear waste treatment and environmental protection. Coordination polymers (CPs) are a family of newly emerging potential iodine absorbents....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Compared with BTCMP‐2, BTCMP‐1 has a higher iodine capacity, which is due to the presence of fluoride moieties and relatively high pore volumes, thus increasing the iodine adsorption capacity of the sample. Although the thiophene‐based polymers BTCMP‐1 and BTCMP‐2 have low specific surface areas and pore volumes, the unique microscopic properties and electron‐rich groups of them in the network skeletons significantly increase the affinity between the polymers and gaseous iodine molecules, and improve the adsorption value, which makes them better at capturing iodine than those of some organic porous materials with high porosity, such as PAF‐1 ( S BET = 5600 m 2 /g, 186 wt%), 21 JUC‐Z2 ( S BET = 2081 m 2 /g, 144 wt%), 27 NIP‐CMP ( S BET = 2600 m 2 /g, 202 wt%), 28 CMPN‐3 ( S BET = 1368 m 2 /g, 208 wt%), 29 and so forth. These results indicated that the electron‐rich groups in the skeleton structures of the polymers were the main factors affecting the iodine adsorption value of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with BTCMP‐2, BTCMP‐1 has a higher iodine capacity, which is due to the presence of fluoride moieties and relatively high pore volumes, thus increasing the iodine adsorption capacity of the sample. Although the thiophene‐based polymers BTCMP‐1 and BTCMP‐2 have low specific surface areas and pore volumes, the unique microscopic properties and electron‐rich groups of them in the network skeletons significantly increase the affinity between the polymers and gaseous iodine molecules, and improve the adsorption value, which makes them better at capturing iodine than those of some organic porous materials with high porosity, such as PAF‐1 ( S BET = 5600 m 2 /g, 186 wt%), 21 JUC‐Z2 ( S BET = 2081 m 2 /g, 144 wt%), 27 NIP‐CMP ( S BET = 2600 m 2 /g, 202 wt%), 28 CMPN‐3 ( S BET = 1368 m 2 /g, 208 wt%), 29 and so forth. These results indicated that the electron‐rich groups in the skeleton structures of the polymers were the main factors affecting the iodine adsorption value of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with monomers 3,3 0 ,5,5 0 -tetrabromo-2,2 0 -benzothiophene = 5600 m 2 /g, 186 wt%), 21 JUC-Z2 (S BET = 2081 m 2 /g, 144 wt%), 27 NIP-CMP (S BET = 2600 m 2 /g, 202 wt%), 28 CMPN-3 (S BET = 1368 m 2 /g, 208 wt%), 29 and so forth. These results indicated that the electron-rich groups in the skeleton structures of the polymers were the main factors affecting the iodine adsorption value of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both excitation and emission spectra of ligand H 2 BPD-4F4TS and ZnBPD-4F4TS were recorded in the solid state (Figure 3a,b). In the case of ligand H 2 BPD-4F4TS, it displays one fluorescent emission band centered at 535 nm when excited at 370 nm, which is probably assigned to π or n to π* orbital transitions [42,43]. After coordination to form ZnBPD-4F4TS, it shows a similar but blue-shifted emission peak at 518 nm when excited at 370 nm, showing a green emission of crystals (Figure 3c).…”
Section: Luminescent Propertiesmentioning
confidence: 95%